Project based learning as a strategy of blended learning in the architecture and urbanism course - Sayd, João Lemos Cordeiro; Canal Filho, Pedro; Costalonga Neto, José Osvaldo (Brazilian Journal of Production Engineering, 2021)
The paper identifies potentialities and limitations of application of the Project Based Learning (PBL) method in the second period of the Architecture and Urbanism course in an institution of higher education, in the context of deepening the blended learning model. In this way, the main theoretical issues involving the PBL method were raised and it was studied two activities developed with students of the second period with the same objective (developing a method / methodology for the execution of architectural projects), in the classroom and blended learning models. Both activities used concepts from this active learning methodology, but with different organizations and themes, to some extent resulting from the migration of the teaching model. The first activity is called “Meu Lugar”, of a playful and individual character and the second activity is an extension project, structured based on a real demand. It was observed that the two strategies are important and complementary, as the “Meu Lugar” project enables the assessment of the individual student, based on personal interests and freer conceptual propositions, while the extension project develops teamwork, service real demands and respect for current legislation and regulations, as well as the desires and needs of a specific recipient. In both cases, it was also noted the need for complementary activities and challenges, which support a technical apparatus, especially representation.
Keywords: Active learning; Extension project; Introduction to architectural project